Assessment of products of different thermochemical processing from anaerobic digestion waste - Diaz Perez, Nidia (2022)
Anaerobic digestion (AD) is widely used to treat low-value organic waste to produce a methane-rich biogas for bioenergy generation. Although it has positive sustainability credentials due to its ability to convert waste to energy, only a relatively small amount of waste fed into AD is converted into biogas, resulting in a large amount of residual solid waste known as digestate. This residue can be used as fertiliser, but only if meets strict regulations for spreading on soil. Characterisation of the waste generated in AD systems was carried out in this research, which led to the primary hypothesis that digestate has the potential to produce more valuable bioproducts if pyrolysis technologies are used in conjunction with AD. Three different pyrolysis were assessed to transform digestate into bio-based products. Fast pyrolysis was studied in collaboration with VTT in Espoo, Finland. Slow pyrolysis and microwave pyrolysis were studied using the available facilities at the University of Nottingham. Considerable differences were found in pyrolysis products from digestate between these three technologies. Slow pyrolysis at operating temperatures between 355-530oC resulted in bio-oil yields of 34-46% and with a large amount of water ranging from 13-19% wt. This pyrolytic liquid was a high-acid product where primary compounds from cellulose and hemicellulose, such as levoglucosan and furfural, were not detected. These results revealed that secondary reactions occurred due to the high ash content. Acetic acid was the most prevalent compound quantified with a significant variation between bio-oil samples analysed. This indicated that ash content in digestate was different in each experiment performed, affecting the subsequent chemical composition of the product. Fast pyrolysis of digestate performed at 460-560oC produced bio-oils with less water (8-11% wt), but with a high-acid concentration. Sugar production was around 2%, higher than slow pyrolysis, yet a little amount compared with the sugar generation from low-ash biomasses that has been processed in the same system. Due to a high-phenolic concentration in both bio-oils resulting from slow- and fast pyrolysis it was concluded that the presence of ash is likely to be favourable for lignin decomposition. Experiments with microwave pyrolysis were performed with dry and wet digestate at the same conditions. The highlight was more aldehydes, ketones, phenolics, and even some levoglucosan and furfural were detected with wet biomass using less power input, along with less acid formation. These results demonstrated that high moisture in digestate could promote lignocellulose depolymerisation with less energy required. However, due to the amount of ash present within digestate any benefit of using this technology appears to be offset by secondary catalytic reactions and further decomposition. Integration of pyrolysis technologies with AD was the main purpose for this research; however an alternative scenario was evaluated whereby crop waste was pyrolysed directly, without being fed into an AD system. Slow pyrolysis of pre-AD crop produced a large amount of primary holocellulose derivatives, with no acetic acid detected, whereas bio-oil resulting from microwave pyrolysis had a high acetic acid concentration and very small amount of sugars. It was found that not only the presence of ash when biomass is pyrolysed has an effect on chemical composition of the products, but any pre-treatment of feedstock significantly influences in how lignocellulose is thermochemically decomposed. A kinetic model was developed to predict the conversion of pre- and post-AD waste into pyrolysis products. A scheme of reactions was modified to reduce the activation energy of biochar, water and small-molecule compounds to promote easier generation in a larger range of ash content. The kinetic model shows that high ash content in biomass could impact not only pyrolysis product yields, but also sugar generation. These results agreed with the experimental data obtained from pyrolysis of pre-AD crop and crop digestate. The high ash content makes pyrolysis of digestate a challenging proposition for a commercial process, irrespective of which technology is used. A third scenario is presented in this project, where digestate from crop- and food waste can be treated in a two-stage process to recover high-value components. Firstly, the aqueous medium resulting directly from post AD can be subjected to a low-temperature treatment with microwave technology to obtain hemicellulose-derived monosaccharides. The second stage consists of an enzymatic processing to depolymerise cellulose into D-glucose to enrich a solution with sugars to be recirculate to the AD system and produce more biogas. Digestate analysed from East Birmingham AD facility (Coleshill) in East Birmingham and Stoke Bardolph in Nottinghamshire in the UK, revealed that every 30g of food-waste digestate has 4g of sugar can be recovered, and every 100g of crop digestate has around 45g of sugar-rich components. This would result in an improvement in biogas production in crop-waste AD systems from 20% to almost 40%, and in food-waste AD from 10% to 20% wt. Final crop digestate would become a lignin-rich biomass and could employed in any thermal technology to obtain a liquid with high phenolic content or to produce other lignin-derived products. Whilst the primary hypothesis was found not to be a viable approach, this study proposes three different schemes as opportunities to recycle and re-use AD waste to decarbonise and promote the circularity of waste processing.